2021
DOI: 10.1111/and.14033
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone improves testicular damage and sperm quality in experimentally varicocele‐induced adolescent rats

Abstract: The aim of this study was to investigate the protective and therapeutic effects of thymoquinone against the negative effects of varicocele on testicular tissue and sperm morphology. Five groups were formed by random selection from a total of 40 adult male Wistar rats (n = 8). Thymoquinone (5 mg/kg/day) was administered intraperitoneally to the varicocele‐dimethyl sulfoxide‐olive oil‐thymoquinone (VT) group and the sham‐thymoquinone group. At the end of the 60th day, all groups were anaesthetised and the left t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Nigella sativa active component thymoquinone (TQ) with good antioxidant properties improves the quality of spermatozoa, decreases defected sperms ( Gur et al, 2021 ) by improving sperm producing mother cells ( Wani et al, 2022 ), sperm motility by maintaining energy pathways in aerobic respiration result in improved fertility ( Inanc et al, 2022 ). Chemically synthesized silver nanoparticles exerted a negative effect on spermatogenesis whereas green synthesis by Nigella sativa exerted positive effects on spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nigella sativa active component thymoquinone (TQ) with good antioxidant properties improves the quality of spermatozoa, decreases defected sperms ( Gur et al, 2021 ) by improving sperm producing mother cells ( Wani et al, 2022 ), sperm motility by maintaining energy pathways in aerobic respiration result in improved fertility ( Inanc et al, 2022 ). Chemically synthesized silver nanoparticles exerted a negative effect on spermatogenesis whereas green synthesis by Nigella sativa exerted positive effects on spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, peritubular myoid cells not only maintain the structural integrity of seminiferous tubules, but also participate in spermatogenesis and regulation of testicular function. Studies have reported that the reticular fibers around the seminiferous tubules in rats can provide support the structure of reproductive epithelium, and experimental varicocele induces hypoxia is frequently accompanied by some degree of testicular fibrosis ( Gur et al, 2021 ). The collagen protein, elastin, proteoglycan and glycoprotein are synthesized by fibroblasts cells and form fibers matrix ( Jia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic index (AI) was defined as the average number of TUNEL-positive cells per seminiferous tubule cross-section as previously described. 26 …”
Section: Methodsmentioning
confidence: 99%